(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In order to dynamically compare the chest circumference depending on the type of sport with the subsequent construction of a sports fitness prediction model, 215 students of higher education institutions of Bukovina were studied. where the primary study was carried out in 2021 and a repeated study of these same students a year later (2022). The main group consists of 175 students of the Faculty of Physical Culture, Sports and Rehabilitation of Yuriy Fedkovych Chernivtsi National University and the control group consists of 40 students of the Bukovina State Medical University. The age of the subjects was 17.45±1.15 years. Among the students of the main group, 46 played football, of whom 25 were young boys and 21 were young girls, 44 students played handball, of whom 24 were young boys and 20 were young girls, 44 students also played volleyball, of whom 24 were young boys and 20 were young girls, 41 students played basketball, of whom 22 were young boys and 19 were young girls. The chest circumference of the studied students was determined during inhalation, exhalation and at rest. To compare the indicators of the respondents during the first measurement and the second one a year later, a paired t-test (paired samples t-test) was conducted. As a result of the studies conducted, comparing the chest circumference during inhalation, exhalation and breath holding according to the primary study, it was found that the chest circumference of the studied students has the greatest statistical difference in students who attended handball sections, unlike other groups. Also, by comparing the dynamics of the parameters of the chest circumference during inhalation, exhalation and during breath holding, it was found that the largest statistical difference in the parameters was during breath holding. By comparing the parameters of the chest circumference during inhalation, exhalation and breath holding, a statistical difference was established between boys and girls. So, models were derived for predicting the chest circumference during inhalation: Chb = β + 0.58*w – 0.206*h, during exhalation: Che = β + 0.588*w, during breath holding: Chbl = β + 0.644*w, where significant predictors for the chest circumference during inhalation are height, weight and gender, for the chest circumference during exhalation and during breath holding, significant predictors are weight and gender.